The importance of pharmacotherapy literacy for communication tailored to people’s needs: public health perspective and interventions - Ubavić, Stana; Krajnović, Dušanka; Lević, Marija (Archives of Pharmacy, 2022)
Pharmacotherapy literacy is literacy in the context of medicines. It represents ability of individuals to find, evaluate, calculate and understand information about medicines, needed for decisions, regardless transmission and content of information (written, spoken, image, symbol) in order to reduce risk of poor pharmacotherapy outcomes. Adequate pharmacotherapy literacy is strategy for proper and safe medicines use. Daily, many people misuse medicines due to inadequate pharmacotherapy literacy. Recently, specific assessment tools and interventions were developed to alleviate patients’ needs for simplification, education, and support during medicines use. The objective of study was to review and present pharmacotherapy literacy researches in the adult population (in healthy individuals and specific patient populations). Previous researches included respondents at population level and in health institutions. It was developed 13 instruments for evaluation of pharmacotherapy literacy, 9 for particular medicines group, and 4 instruments were general. Most instruments included only dimensions of functionality and numeracy. In all populations, predictors of pharmacotherapy literacy levels were: education, age, sex and ability for self-medication. Persons with lower pharmacotherapy literacy need assistance and simpler information when dispensing medicines. As a guideline for identifying patients with lower pharmacotherapy literacy, a RALPH (Recognize and Address Limited Pharmaceutical Literacy) interview was created to support pharmacists for easier identification of patients with limited literacy. The number of pharmacotherapy literacy studies is rising. Pharmacists, as the most accessible health professionals, have key role in reducing patient confusion and improving pharmacotherapy literacy, through communication tailored to their needs, after identification of pharmacotherapy literacy levels.